POTATO VIRUS X FROM PAKISTAN: COAT PROTEIN SEQUENCE ANALYSIS - A. Khan; B. Tabassum; I. A. Nasir; M. Bilal; M. Tariq; T. Husnain (Journal of Animal and Plant Sciences, 2015)
Potato virus X (PVX) a most devastating pathogen of potato, tomato and tobacco all over the world was surveyed for its epidemics in Pakistan. A 891bp amplicon covering full capsid protein gene of potato virus X was amplified through reverse transcription-polymerase chain reaction by using gene speciﬁc primers from the samples collected all over Punjab, Pakistan. Deduced sequence of full capsid protein gene of PVX was reported as the first full length coat protein gene of potato virus X from Pakistan in NCBI database (Accession # KC757709). In phylogenetic analysis, Pakistani PVX isolate was found to be clustered closely with European sub linage while distinctly with Australian PVX and South American isolates. In contrast to the nucleotide sequence the amino acid sequence dendrogram of PVX, Pakistani isolate showed 100% homology with American isolates. Conclusively, a new isolate of PVX was identified from Pakistan which surprisingly exhibited close lineage with European isolate.
Keywords: Potato Virus X; Capsid protein gene; Phylogenetic analysis; Reverse Transcription; amino acid sequence dendrogram